2017
DOI: 10.7897/2277-4572.06147
|View full text |Cite
|
Sign up to set email alerts
|

Aqarqarha (Anacyclus Pyrethrum Dc.) a Potent Drug in Unani Medicine: A Review on Its Historical and Phyto-Pharmacological Perspective

Abstract: Aqarqarha (Anacyclus pyrethrum DC.) is a very famous botanical origin drug in Unani system of medicine. It is used since antiquity. It is described by Dioscorides, Galen, Avicena, Avenzoar, Ishaque bin Imran. According to Galen use of this drug is beneficial in chronic Paralysis, Khadar (numbness), toothache, intermittent fever. Rhazes and other Unani physician used it for strengthening the teeth, easy extraction of the teeth, paralysis, facial palsy, epilepsy, colitis, muqawwi-i-bah (aphrodisiac), mharrik-iba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The unani physician used this drug for thousands of years, Dioscorides (1 st century), Ibn Sina, Ishaque bin Imran, Jalinus (131-210 AD), and Marwan bin Zohar, referred to akarkara in their books [13].…”
Section: Historical Backgroundmentioning
confidence: 99%
“…The unani physician used this drug for thousands of years, Dioscorides (1 st century), Ibn Sina, Ishaque bin Imran, Jalinus (131-210 AD), and Marwan bin Zohar, referred to akarkara in their books [13].…”
Section: Historical Backgroundmentioning
confidence: 99%
“…Therefore, by blocking both receptors of GABAergic system by PTZ as a selective antagonist of GABA A receptors and Phaclofen as a selective antagonist of GABA B receptors was tried to determine the possible mechanism of APE on GABAergic system. Recently, people tend to take traditional remedies more than synthetic drugs, because they believe that such herbal medicines have fewer side effects and are cheaper than synthetic drugs [14]. Anacyclus pyrethrum with different names, such as Aqarqarhaa in Greek, Persian, Indianan and Arabic, or Pellitory in English and Akarkara in Hindu, is considered a valuable herb in traditional medicine [15].…”
Section: Introductionmentioning
confidence: 99%
“…This plant can be harvested twice a year (June and April), but it might contain different components according to the time of harvest [15,16]. Toxicity studies in animal model have shown that consumption of Anacyclus pyrethrum plant up to 2 g per kg/body weight is safe [14,18,19]. Administration of the ethanolic extract of Anacyclus pyrethrum was previously reported to cure epileptic seizures induced by maximum electric shock [15,18].…”
Section: Introductionmentioning
confidence: 99%